2014
DOI: 10.1111/bph.12488
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral interactions between cannabinoid and opioid systems contribute to the antinociceptive effect of crotalphine

Abstract: BACKGROUND AND PURPOSECrotalphine is an antinociceptive peptide that, despite its opioid-like activity, does not induce some of the characteristic side effects of opioids, and its amino acid sequence has no homology to any known opioid peptide. Here, we evaluated the involvement of the peripheral cannabinoid system in the crotalphine effect and its interaction with the opioid system. EXPERIMENTAL APPROACHHyperalgesia was evaluated using the rat paw pressure test. Involvement of the cannabinoid system was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…These authors demonstrated that crotalphine-induced antinociception stimulates local release of dynorphin A, which is dependent on CB 2 receptor activation [32]. In contrast, we observed the participation of the CB 1 receptor in PnPP-19-induced central antinociception, and as previously reported, μ and δ opioids receptors are also involved [17].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These authors demonstrated that crotalphine-induced antinociception stimulates local release of dynorphin A, which is dependent on CB 2 receptor activation [32]. In contrast, we observed the participation of the CB 1 receptor in PnPP-19-induced central antinociception, and as previously reported, μ and δ opioids receptors are also involved [17].…”
Section: Discussionsupporting
confidence: 80%
“…Recently, it was shown that peripheral interactions between cannabinoid and opioid systems contribute to the antinociceptive effect of the peptide crotalphine [32]. These authors demonstrated that crotalphine-induced antinociception stimulates local release of dynorphin A, which is dependent on CB 2 receptor activation [32].…”
Section: Discussionmentioning
confidence: 99%
“…The contribution from Machado et al (2014) assessed cross-talk between the cannabinoid and opioid systems in pain management. The authors investigated the cannabinoid-mediated anti-nociceptive activity of crotalphine, a synthetic peptide with opioid-like activity, following induction of hyperalgesia in rats via intraplantar administration of prostaglandin E2.…”
Section: Linked Articlesmentioning
confidence: 99%
“…Konno et al, 2008;Zambelli et al, 2014). Some of its actions are mediated through k-opioid receptors, with an involvement of pathways including nitric oxide (Gutierrez et al, 2012) and cannabinoids (Machado et al, 2014). Crotalphine is being treated as a possible development candidate (US Patent Application, 2009) and is currently in the pre-clinical phase with the Brazilian company Biolab Farmaceutica.…”
Section: Still To Come?mentioning
confidence: 99%